Infraestructura arquitectónica y logística de transporte territorial en líbano – Tolima (2023)
The objective of this work is to solve the problem in the municipality of Líbano related to the lack of a space for intermunicipal, interveredal, interurban transport and agricultural product transportation, which has caused vehicular congestion in places like the main park and market square. To achieve this, a study of mobility and transportation is conducted, and an architectural and logistical transport infrastructure is proposed in the municipality.